The Enhancement of Science in Children Through B4 Group Vegetable Planting Activities on Odd Semester at Pertiwi Kindergarten Metro Studying Year 2017-2018 - Muchsonny Muchsonny; Rizky Hidayatullah; Muhammad Saidun Anwar (SELING: Jurnal Program Studi PGRA, 2019)
This research was conducted to find out the extent of the benefits of growing vegetables to increase the science recognition of children in the Pertiwi Metro Kindergarten B4 group. The problem discussed in this research are the benefits of growing vegetables to increase science recognition to children in group B4. This research uses Classroom Action Research (CAR) with 2 cycles. Each cycle there are 4 stages: planning, action, observation, and reflection. The object of the research was carried out at the Metro Pertiwi Kindergarten 2017-2018 Academic Year. The data collection tool used in this research was direct observation with the steps of data collection, data analysis, and drawing conclusions to find out the benefits of growing vegetables to increase science recognition in children and analyzed descriptively. This research is expected to have impact children are more capable, more conscientious, happier and more confident in following the learning process. especially in the introduction of science.